MON-073 Hyperinsulinemic Hypoglycemia Responsive to Diazoxide Due to a Previously Unknown ABCC8 Dominant Mutation - Figueredo, Veronica M (J Endocr Soc, 2020)
Background: Hyperinsulinism is the most common cause of persistent hypoglycemia. It results from different genetic defects, the most common being recessive and dominant mutations in the ABCC8/KCNJ11 genes. The majority of recessive mutations have a poor response to Diazoxide, while dominant mutations are highly variable in both clinical presentation and response to treatment. Prompt recognition and management is critical to avoid irreversible brain damage. Clinical case: A 38-week gestation male, born via emergent c-section due to decreased fetal movement, presented with neonatal hypoglycemia. Pregnancy was uncomplicated and mother had a normal OGTT. Patient had a history of suspected sepsis, seizures, pulmonary hypertension and respiratory distress requiring intubation. Blood glucose was undetectable at birth and required multiple dextrose 10% boluses. A critical sample with a glucose of 47 mg/dL showed an elevated insulin at 30.3 m IU/mL with undetectable ketone levels. Lactic acid, ammonia, cortisol, GH, plasma amino acids, acylcarnitine profile and uric organic acids where all normal for a hypoglycemic state. He required intravenous glucose infusion with GIR up to 17 mg/kg/min to maintain normoglycemia. A brain MRI at 11 days of life showed findings of white matter injury. Subsequent genetic testing identified a heterozygous c.4051G>A (p.Val1351Met) variant in ABCC8, classified as “of uncertain significance”. However, an entry in the ClinVar database (RCV000714711.1) exists from a research lab and was classified as likely pathogenic. Analysis of parental samples showed that the mother was heterozygous for the same genetic variant. She did not have a history of hypoglycemia. Patient was started on diazoxide (8 mg/kg/day) and chlorothiazide with resolution of hypoglycemia. At a follow up visit at 5 months of age, there was no history of hypoglycemia, and no need for adjustments of the diazoxide dose by weight (dose at that time of 7.4 mg/kg/day). Conclusion: The ABCC8 reported here is a dominant mutation causing hyperinsulinemic hypoglycemia responsive to diazoxide with a milder phenotype later in infancy. Longitudinal follow up of the case is warranted to understand the long term progress in patients with this particular mutation. Reference: Adam MP, Ardinger HH, Pagon RA, Wallace SE, et al. None. 1993. Familial hyperinsulinism.